2008
DOI: 10.1111/j.1467-9450.2008.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childhood bilingualism on episodic and semantic memory tasks

Abstract: Kormi-Nouri, Moniri and Nilsson (2003) demonstrated that Swedish-Persian bilingual children recalled at a higher level than Swedish monolingual children, when they were tested using Swedish materials. The present study was designed to examine the bilingual advantage of children who use different languages in their everyday life but have the same cultural background and live in their communities in the same way as monolingual children. In four experiments, 488 monolingual and bilingual children were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
6
36
0
1
Order By: Relevance
“…In the free recall test, which is a more effortful task, both semantic integration (wellintegrated items) and episodic integration (SPT encoding) are required for good memory performance. In cued recall and recognition tests, which are less effortful tasks, only the effect of enactment improves memory performance (Kormi-Nouri, 1995;Kormi-Nouri & Nilsson, 1998;Kormi-Nouri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the free recall test, which is a more effortful task, both semantic integration (wellintegrated items) and episodic integration (SPT encoding) are required for good memory performance. In cued recall and recognition tests, which are less effortful tasks, only the effect of enactment improves memory performance (Kormi-Nouri, 1995;Kormi-Nouri & Nilsson, 1998;Kormi-Nouri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…That is, half of the participants in each of the encoding conditions received real objects, whereas the other half were instructed to act on an imaginary object control the effect of the object's presence. This was based on the results of previous studies in action memory that showed some differences between adult and child populations with respect to the presence of an object (Kormi-Nouri, 2000;Kormi-Nouri, et al, 2008). Some studies of adults have shown that there is no significant difference among participants' performances when either real objects or imaginary objects are presented (Kormi-Nouri, 2000), whereas, in children, SPTs with real objects corresponded to a higher performance than imaginary objects (Kormi-Nouri et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Carr, Castel, & Knowlton, 2015;Hülür, Hertzog, Pearman, & Gerstorf, 2015, Lee, Ning, & Goh, 2014. Kormi-Nouri et al (2008) poukázali na lepšiu sémantickú i epizodickú pamäť bilingválnych v porovnaní s monolingválnymi, pričom táto výhoda sa ukázala v oboch jazykoch dvojjazyčných. Toto zistenie sa v našom výskume nepotvrdilo.…”
Section: Diskusiaunclassified
“…According to the revised hierarchical model (Kroll and Stewart, 1994; Kroll et al, 2010), lexical connections between the two languages in bilinguals are linked to common conceptual memory representations; and the connections to conceptual memory depend on bilinguals' L1 and L2 experiences and knowledge. In the same vein, evidence regarding bilinguals' language knowledge in two languages, bilinguals' episodic memory, and their semantic memory (e.g., Francis, 1999; Kormi-Nouri et al, 2003, 2008, 2012; Sheng et al, 2006, 2013; Bialystok and Feng, 2009) suggests that bilinguals differ from monolinguals in how they encode, retain, and organize words.…”
Section: Introductionmentioning
confidence: 99%